(untitled) (Research, Society and Development, 2020)
The risk of health professionals exposed to different incidents associated with care, can cause damage to their health and that of their families, depending on the culture and institutional actions. The present study aims to: Propose a reflection on safety in professional practice, facing Covid-19, in the context of hospital care, considering Brazilian standards. It is a reflection article on health and safety measures for workers working in institutions for assistance, regulated by the Regulatory Norms of the Ministry of Labor and Employment of Brazil. The results are presented in two categories: 1. Exposure by health professionals and preventive measures to Covid-19; recommendations for the use of Personal Protective Equipment (PPE), as well as policies that mitigate exposure to these professionals to infection, must be prepared. 2. Identification and management of the worker’s exposure risk; categorize the risk of each health professional after exposure to a patient with Covid 19 and proceed with the management of the professionals. 3. Worker safety and working conditions in Brazil; the pandemic exacerbated the condition of unhealthy work that health professionals experience on a daily basis and, as a consequence, aggravates exposure to other occupational risks, due to the precariousness of material necessary for the attention of users, and the work overload. Given the current scenario, it is necessary to carry out actions based on protocols and standards, aiming at the health of the population and professionals.